Development of Digital Comics on the Human Excretory System as a Learning Resource - Erica Yosefunny Hutagalung; Eko Prasetya (Florea : Jurnal Biologi dan Pembelajarannya, 2026)
This study aims to develop learning media in the form of digital comics on the subject of the excretory system for 11th grade high school students. The study uses the Research and Development (R&D) method. The sampling technique used is Random Sampling. The research sample is class XI-MIA 1, consisting of 32 students. The instruments used in this study included interview guidelines, questionnaires, and multiple-choice tests in the form of pre-tests and post-tests, each consisting of 30 questions. The data were analyzed qualitatively to examine the feasibility of the media and user responses, as well as quantitatively using N-gain calculations to measure the effectiveness of the learning media. Based on the results of data analysis, digital comics were declared very feasible for use as learning media, with an average score of 4.40 from media experts, 4.82 from subject matter experts, 4.80 from learning experts, and a teacher assessment of 86.5%. Based on the N-gain test analysis, there was an increase in the average score from 56.88 on the pretest to 84.88 on the posttest, with an N-gain value of 0.6492 (64.92%). These results indicate that the learning media is effective.